Deep economy the wealth of communities and the durable future - McKibben, Bill (New York Times Books / Henry Holt and Company, 2008)
An impassioned call for an economy that creates community and ennobles our lives. In this manifesto, journalist McKibben offers the biggest challenge in a generation to the prevailing view of our economy. For the first time in human history, he observes, "more" is no longer synonymous with "better"--indeed, they have become almost opposites. McKibben puts forward a new way to think about the things we buy, the food we eat, the energy we use, and the money that pays for it all. Our purchases, he says, need not be at odds with the things we truly value. McKibben's animating idea is that we need to move beyond "growth" as the paramount economic ideal and pursue prosperity in a more local direction, with regions producing more of their own food, generating more of their own energy, and even creating more of their own culture and entertainment.--From publisher description.
After growth -- The year of eating locally -- All for one, or one for all -- The wealth of communities -- The durable future.
"Originally published in hardcover in 2007 by Times Books"--Title page verso.
KSSP-2902 donated by Prof. Michael L. Tan, Chancellor University of the Philippines Diliman.
Keywords: Economic development -- Social aspects; Community development